The Role of Outcome Forecasts in Patients' Treatment Decisions-Evidence from a Survey Experiment on Knee Replacement Surgery - Kesternich, Iris; Caro, Francis G.; Gottlieb, Alison S.; Hoffmann, Susanne; Winter, Joachim K. (Health services research, 2016)
Objective To analyze the effect of personalized outcome probabilities on treatment decisions. Data Source American Life Panel. Study Design We designed an experimental survey that respondents answered by recommending replacement surgery for hypothetical patients diagnosed with knee osteoarthritis. The primary manipulation was whether respondents were given personalized outcome probabilities for the patients. Principal Findings Patient‐specific outcome forecasts significantly influenced decisions, with effect sizes comparable to those of physicians' opinions and patient testimonials. The presentation format also affected the probabilities' influence on choices. We did not find evidence that the educational level of subjects affected the weight that they give to outcome probabilities in making recommendations. Conclusion Our study points to a need for more research on the use of patient‐specific outcome forecasts.